Ethnic differences in lifetime cumulative incidence of syncope: the Malaysian elders longitudinal research (MELoR) study - Tan, Maw Pin; Ho, Yun Ying; Chin, Ai-Vyrn; Saedon, Nor 'Izzati; Abidin, Imran Zainal; Chee, Kok Han; Khor, Hui Min; Goh, Choon Hian; Hairi, Noran Naqiah; Othman, Sajaratulnisah; Kamaruzzaman, Shahrul Bahyah (Springer, 2020)
Purpose: To determine the lifetime cumulative incidence of syncope, potential ethnic differences and factors associated with syncope using the Malaysian elders longitudinal research (MELoR) study first wave dataset. Methods: The MELoR study recruited community-dwelling adults aged 55 years and over, selected through stratified random sampling from three parliamentary constituencies. The baseline data collected during the first wave was obtained through face-to-face interviews in participants’ homes using computer-assisted questionnaires. During their baseline assessments, participants were asked whether they had ever experienced a blackout in their lifetime and if they had experienced a blackout in the preceding 12 months. Results: Information on blackouts and ethnicity were available for 1530 participants. The weight-adjusted lifetime cumulative incidence of syncope for the overall population aged 55 years and above was 27.7%. The estimated lifetime cumulative incidence according to ethnic groups was 34.6% for Malays, 27.8% for Indians and 23.7% for Chinese. The estimated 12-month incidence of syncope was 6.1% overall, equating to 11.7% for Malays, 8.7 % for Indians and 2.3% for Chinese. Both Malay [odds ratio (OR) 1.46; 95% confidence interval (CI) 1.10–1.95 and OR 3.62, 95% CI 1.96–6.68] and Indian (OR 1.34; 95% CI 1.01–1.80 and OR 3.31, 1.78–6.15) ethnicities were independently associated with lifetime and 12-month cumulative incidence of syncope, respectively, together with falls, dizziness and myocardial infarction. Conclusion: Ethnic differences exist for lifetime cumulative incidence of syncope in community-dwelling individuals aged 55 years and over in an urban area in Southeast Asia. Future studies should now seek to determine potential genetic, cultural and lifestyle differences which may predispose to syncope. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.